Wi-Fi Enabled Healthcare - Youssef, Ali (Taylor & Francis, 2014)
Focusing on the recent proliferation of Wi-Fi in hospital systems, this book explains how Wi-Fi is transforming clinical work flows and infusing new life into the types of mobile devices being implemented in hospitals. Drawing on years of consulting with hospitals in the US and abroad, and with first-hand experiences from one of the largest healthcare systems in the United States, it covers the key areas associated with wireless network design, security, and support. Reporting on cutting-edge developments and emerging standards in Wi-Fi technologies, the book explores security implications for each device type. It covers real-time location services and emerging trends in cloud-based wireless architecture.